Integrated assessment of the quality of microprocessor-based relay protection - Ramsh, V.; Potapenko, M.; Sharshon, V. (Energy and Automation, 2025)
The article discusses the problems of assessing the effectiveness of microprocessor-based relay protection of power system facilities. The relevance of the study is due to the importance of relay protection devices in ensuring timely detection and elimination of emergency modes, preventing equipment damage, and maintaining the stability of the power system. Traditional approaches to assessing performance quality boil down to taking into account equipment and operational losses or are limited to the percentage of correct relay actions, which does not always allow for an accurate assessment of system efficiency.The purpose of the study is to develop an integrated criterion for evaluating the effectiveness of microprocessor-based relay protection, which takes into account functional and metrological losses caused by measurement errors, response delays, and other features of the implementation of protection algorithms.To analyze losses, it is proposed to classify them into groups: functional-metrological, related to the adjustment of settings and the properties of selectivity and sensitivity; indirect hardware, arising from component failures and personnel errors; independent of settings, including damage to equipment and infrastructure.For quantitative assessment of effectiveness, an integral indicator  is proposed, which takes into account all elements of the relay protection channel and allows assessing the probabilistic characteristics of losses and the potential effect of protection. To assess reliability, a normalized failure rate  is used, which includes relay failures, incorrect protection actions, and personnel errors.An integrated approach allows for a comprehensive assessment of the efficiency, technical excellence, and economic feasibility of using microprocessor relay protection devices, predicting their behavior in emergency situations, optimizing settings, and increasing the adaptability and reliability of the system in real operating conditions. The use of the probabilistic-statistical method ensures objectivity of assessment and allows making informed decisions on the modernization and optimization of relay protection systems for power facilities.Key words: wind power installation, wind potential, wind speed, repeatability of wind speeds, distribution function, forecasting